PLP1-lacZ transgenic mice reveal that splice variants containing “human-specific” exons are relatively minor in comparison to the archetypal transcript and that an upstream regulatory element bolsters expression during early postnatal brain development - Patyal, Pankaj; Fil, Daniel; Hamdan, Hamdan; Wight, Patricia A. (Frontiers in Cellular Neuroscience, 2023)
Much of what is known about the mechanisms that control the developmental expression of the myelin proteolipid protein gene (PLP1) has been attained through use of transgenic animal models. In this study, we analyzed expression of related transgenes which utilize PLP1 genomic DNA from either human or mouse to drive expression of a lacZ reporter. Human PLP1 (hPLP1) sequence span either the proximal 6.2 or 2.7 kb of 5ʹ-flanking DNA to an internal site in Exon 2, while those from mouse comprise the proximal 2.3 kb of 5ʹ-flanking DNA to an analogous site in Exon 2. Transgenes with hPLP1 sequence were named, in part, to the amount of upstream sequence [6.2hPLP(+)Z/FL and 2.7hPLP(+)Z]. The transgene containing mouse sequence is referred to here as mPLP(+)Z, to denote the species origin of PLP1 DNA. Mice which harbor the 6.2hPLP(+)Z/FL transgene were used as a model system to investigate the developmental expression of splice variants that incorporate supplementary exons from what is classically defined as PLP1 intron 1. While expression of the splice variants were detected in brain through RT-PCR analysis, they are present at much lower levels relative to the archetypal (classic) transcript. Additionally, we show that mice which harbor the 6.2hPLP(+)Z/FL transgene demonstrate wide-ranging expression throughout brain at P2, whereas expression of mPLP(+)Z is quite limited at this age. Therefore, we generated new transgenic mouse lines with the 2.7hPLP(+)Z transgene, which contains hPLP1 sequence orthologous to just that in mPLP(+)Z. Expression of the 2.7hPLP(+)Z transgene in brain was comparatively lower at P2 than P21, indicating that the distal 3.5 kb of 5ʹ-flanking PLP1 DNA specific to 6.2hPLP(+)Z/FL contains regulatory element(s) important for promoting early postnatal expression in brain.